全球化背景下藏族农村社区的 语言生活——青海省黄南藏族 自治州力加村语言使用及语言 态度研究 = The Language Life in a Tibetan Village Community with Globalization: Case Study on Language Use and Attitude in Lijia Village, Huangnan, Qinhai (Sinología hispánica. China Studies Review, 2015)
采用问卷调查、辅以访谈的方式，调查藏语安多方言区的一个农业社区（力加村）的语言生活、语言活力、语言使用和语言态度。结果显示，当地藏语文活力旺盛，藏语是当地各种场合的主要交际用语。被调查对象中近一半人是藏汉双语人，他们大多年龄较小或受过教育。被调查对象的语言文字态度具有较强的包容性，对藏汉语文都持积极态度。所有被调查对象都希望后代接受藏语教育，近一半被调查对象希望后代在接受藏语教育的同时接受汉语 和（或）英语教育。被调查对象对藏语具有很强的民族情感。他们承认藏语文在当地活力旺盛，但仍旧担心“政府制定的语言文字政策执行不到位”会影响当地的藏语文发展。In order to study language vitality, languageuse and language attitude in a Tibetanagriculture community (Lijia Village) in Amdodialect region, the research methodsQuestionnaire and Interview are used to collectdata. The research finds that the TibetanLanguage which is the main communicationlanguage in local area is full of vitalities. Allsubjects hope their children access Tibetaneducation. At the same time, half of thesubjects hope their children access Chinese or(and) English education and become bilingualism. The research also finds that half ofthe subjects are Chinese-Tibetan bilingualism,who are young and (or) educated; and most ofthe subjects hold the positive attitudes towardsboth Chinese and Tibetan